Language Game As An Alternative Model To Improve Arabic Vocabulary Ability - Mahyudin Ritonga; Apri Wardana Ritonga; Sri Wahyuni; Julhadi Julhadi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Vocabulary wealth for every learner is a must. Without an extensive vocabulary, it will hinder the ability to speak, but in reality, learners of Arabic. Therefore, this study will reveal language games as an alternative to improving Arabic vocabulary skills. The research was conducted at Tahfizh Al-Qur'an Daarul Ukhuwah Elementary School Malang, Indonesia, using a descriptive qualitative approach. Data were collected through Google Forms and guided interviews with 30 grade 1 and 3-grade students and 4 Arabic teachers. The data collected were analyzed through the stages of reducing, presenting, and concluding. The results of this study indicate that the language game